Is carsharing for everyone? Understanding the diffusion of carsharing services. (April 2018) - Namazu, Michiko; MacKenzie, Don; Zerriffi, Hisham; Dowlatabadi, Hadi
Abstract: Carsharing (CS) has gained attention as a measure to reduce vehicle ownership, motivate multimodal mobility and cut greenhouse gases and other pollutants. Some municipalities have adopted specific regulations to support adoption of CS. Initial studies, reflecting outcomes from early adopters, have confirmed the expected effects of CS on reduced car ownership and GHG emissions associated with mobility. This study addresses three questions: a) are early adopters sensitive to one-way vs. two-way carsharing? b) do early and late adopters have different household characteristics? and c) can outcomes associated with early adopters be projected onto later adopters? Our study is based on a 2013 survey of residents in 110 apartment buildings in Metro Vancouver, Canada. 2011 responses were analyzed for possible differentiating factors for early adopters at the household level. We find that early adopters (24% of respondents) have more wage-earners per household, live with fewer older family members in neighbourhoods with better CS access and own fewer cars. Among non-CS membership holders (76% of respondents), roughly one-third stated they would never choose CS. The rest expressed interest in joining if CS accessibility was improved and usage/membership fees were lowered. These households are dissimilar to early adopters; they are more likely to live with elderly family members and to own automobile(s) while less likely to have multiple wage earners in their households. The specific characteristics and circumstances of early CS adopters mean that as CS memberships expand, the past patterns of vehicle utilization, car-shedding, vehicle kilometres travelled shifts, and greenhouse gas reductions may not be replicated. Further investigations are required before concluding that the long-term effects of CS services align with observed benefits to date. Highlights: Early carsharing adopters and future adopter had different household demographics and vehicle ownership status. Future adopters of carsharing may not have the same levels of changes in vehicle ownership and VKT compared to early adopters. The diffusion of carsharing services is dynamic rather than static. Further studies, in particular long-term studies are required to maximize the benefits from carsharing services. Policy makers should be aware of the importance of up-to-date data collection/analyses and frequent regulation updates.